2021
DOI: 10.1002/pc.26268
|View full text |Cite
|
Sign up to set email alerts
|

MWCNT, nano‐silica, and nano‐clay additives effects on adhesion performance of dissimilar materials bonded joints

Abstract: Large vehicles, ships, and airplanes are made of hybrid structures with a combination of metal and composite materials. Aluminum and fiber composites are widely used in the aerospace, automotive, and marine industries due to their high strength/weight ratios. In these industries, adhesive joints are preferred as the primary method of forming structural joints. Although the use of adhesives in a combination with different materials provides many advantages over mechanical methods, efforts are being made to incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 46 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Aluminum and fiber composites are widely used in the automotive due to their high strength/weight ratios. [ 3 ] Adhesive joints are preferred as the primary method of forming structural joints, mainly used to transfer uniform load or bear shear load of non‐main bearing parts, such as body panels, etc. The advantages of adhesive joining are very obvious, mainly the advantages of no stress concentration, high‐joining efficiency, light structure, insulation corrosion and other advantages, but also because of its low‐joining strength, easy to peel damage, aging and other disadvantages restrict the development and promotion of bonding.…”
Section: Adhesive Processmentioning
confidence: 99%
“…Aluminum and fiber composites are widely used in the automotive due to their high strength/weight ratios. [ 3 ] Adhesive joints are preferred as the primary method of forming structural joints, mainly used to transfer uniform load or bear shear load of non‐main bearing parts, such as body panels, etc. The advantages of adhesive joining are very obvious, mainly the advantages of no stress concentration, high‐joining efficiency, light structure, insulation corrosion and other advantages, but also because of its low‐joining strength, easy to peel damage, aging and other disadvantages restrict the development and promotion of bonding.…”
Section: Adhesive Processmentioning
confidence: 99%
“…Table 2. Properties for Araldite 2014-1 adhesive [31,32] The bonding region is 40x40mm, and the thickness of the adhesive layer is 0.1 mm [33][34][35]. A fixture was used to ensure keeping the adhesive thickness constant for all adhesively bonded samples.…”
Section: Test Specimenmentioning
confidence: 99%
“…The findings of the research showed that the inclusion of nanoparticles resulted in improved mechanical characteristics. 16,17 Various surface pretreatments are employed to prepare the surface prior to material joining, resulting in significant time and energy consumption. 18 The failure strength of a cocured (CC) composite hat-stiffened panel was higher when using a metal mold, rubber mold, or inflatable mold compared to the strength achieved through co-bonding or secondary bonding methods.…”
Section: Introductionmentioning
confidence: 99%